Leadership Strategies of Patemon Village Head and UINSA KKN 93 Team in Raising Residents' Awareness of Environmental Cleanliness in Probolinggo - Henindya, Titis Emma; Thohir, Muhammad; Mardiyah, Mardiyah (Jurnal Pengabdian Nusantara, 2024)
This study aims to explor the leadership strategy of the Head of Patemon Village in increasing community awareness of environmental cleanliness. This study uses a qualitative method with a descriptive approach, where data is collected through interviews, observations, and documentation. The results of the study indicate that the Head of Patemon Village plays an important role in mobilizing community participation through various strategies, such as socialization, education, waste management training, mutual cooperation, and enforcement of regulations. This leadership has a positive impact, as seen from the decrease in cases of dengue fever and asthma, as well as the improvement of the village's environmental conditions. In conclusion, the leadership of the village head acts as an agent of positive change, especially in increasing community awareness and participation in environmental issues, especially cleanliness.